Skin manifestations in COVID‐19 patients, state of the art. A systematic review. (2nd February 2021) - Perna, Andrea; Passiatore, Marco; Massaro, Antonio; Terrinoni, Alessandro; Bianchi, Luca; Cilli, Vitale; D'Orio, Marco; Proietti, Luca; Taccardo, Giuseppe; De Vitis, Rocco
Abstract: Introduction: Since COVID‐19 has become a pandemic, extensive literature has been produced. The commonest symptoms of COVID‐19 disease are fever, cough, anosmia, and lymphocytopenia. However, other apparently less common clinical symptoms have been described, including skin lesions. We conducted a systematic review to evaluate skin involvement in COVID‐19. Methods: The authors performed a systematic review of literature, in accordance with the Preferred Reporting Items for Systematic and Meta‐Analysis (PRISMA). The search was reiterated until May 06, 2020. Results: Overall, 1593 patients (M/F ratio: 1 : 9) with suspect of COVID‐19 were examined. The mean age was 37.8 (range 0–91) years. Among the analyzed patients, 84 (5.3%) were pediatrics (<18 years). Chilblains are very common among skin lesions and represent almost half of all skin lesions reported (46%); in 75% of patients with cutaneous manifestation, the latter presented before other typical clinical manifestation of COVID‐19. Vasculitis or thrombosis was identified in almost 70% of patients who suffered from skin manifestations. Conclusion: The present study highlights the importance of skin involvement in COVID‐19. Limbs should be examined to eventually foresee the onset of further typical symptoms. Chilblains can be considered typical features. Studies with higher scientific evidence are required.